Supernatural surveillance and blood-borne disease in Bram Stoker's Dracula: Reflections on mesmerism and HIV. (1st November 2019) - Pheasant-Kelly, Fran
AbstractSurveillance and/or voyeuristic viewing are central to certain horror productions and are often related to control and dominance. While such modes of looking are usually less obvious in the vampire film, the vampiric gaze nonetheless exerts a more definitive and immediate effect, causing its victims to fall prey to inevitable death and an extended afterlife. Although all vampire films tend to exploit these mesmeric aspects of Victorian culture, Bram Stoker's Dracula (1992), directed by Frances Ford Coppola, progresses the notion of 'supernatural surveillance'. Coppola uses numerous creative visual techniques to accentuate the attention to eyes, notably in scenes that are linked to sexual desire and promiscuity. If the original novel implicitly reflected contemporaneous fears of venereal infection, namely syphilis, then Coppola's film is preoccupied with AIDS. This essay argues that the film's attention to eyes and the gaze not only reflects the mesmerism associated with Victorian culture but also resonates with new forms of socio-cultural watchfulness emerging in the AIDS era of the twentieth century.